(5, 6‐Dihydro‐1, 4‐dithiin‐2‐yl)methanol as a Versatile Allyl‐Cation Equivalent in (3+2) Cycloaddition Reactions. (6th October 2016) - Hullaert, Jan; Winne, Johan M.
Abstract: The title heterocyclic alcohol readily generates a sulfur‐substituted allylic cation upon simple treatment with a protic acid, thus facilitating a synthetically useful stepwise (3+2) cycloaddition reaction pathway with a range of conjugated‐olefin‐type substrates. The introduction of an allyl fragment in this way provided rapid access to a variety of cyclopentanoid scaffolds. The cyclic nature of the cation precursor alcohol was shown to be instrumental for efficient cycloaddition reactions to take place, thus indicating an attractive strategy for controlling the reactivity of heteroatom‐substituted allyl cations. The formal cycloaddition reaction is highly regio‐ and stereoselective and was also used for a short total synthesis of the natural product cuparene in racemic form through a cycloaddition–hydrodesulfurization sequence.